Illusions in Truth Seeking: The Perils of Interrogation and Torture in the War on Terror - Welch, Michael (Social justice, 2010)
The article discusses the way that the study of science was used by the U.S. government to justify police interrogation and torture in the War on Terror. Discussion of the psychological aspects of interrogation of terror suspects is included. Details of the police science and technology used in the physical torture of suspects are provided. Other topics include U.S. attitudes towards torture of terrorist suspects after the September 11, 2011 Terrorist Attacks, the avoidance of the rule of law by police, and the use of scientific discourse to justify the abuse of suspects.